Lithium-containing multi-metal composite hydrocarbon derivative polymer coating as well as preparation method and application thereof

By constructing a lithium-containing polymetallic composite hydrocarbon-derived polymer coating on the surface of the positive electrode material of lithium-ion batteries, the problems of volume changes and interface side reactions of the positive electrode material during circulation are solved, and higher mechanical and interface stability are achieved, and the cycle stability and rate performance of the battery are improved.

CN119608527APending Publication Date: 2025-03-14GUANGDONG YUANNENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538912.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The positive electrode material of lithium-ion battery faces volume changes and unstable interface side reactions during the cycle process, and the existing polymer coating has low ionic conductivity, resulting in insufficient mechanical stability and interface stability.

Method used

The lithium-containing polymetallic composite hydrocarbon-derived polymer coating is constructed on the surface of the positive electrode material through molecular layer deposition technology. The coating contains lithium elements and a variety of metal elements, such as Al, Zn, Ti, Sn, Hf, V, Zr, Nb, Ta, to form a hybrid film with a metal center and an organic ligand.

Benefits of technology

The mechanical stability and interface stability of the positive electrode material are improved, the ion transport at the electrode interface is promoted, and the cyclic stability and rate performance of the positive electrode are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608527A_ABST
    Figure CN119608527A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-containing multi-metal composite hydrocarbon derivative polymer coating, and discloses a preparation method of the lithium-containing multi-metal composite hydrocarbon derivative polymer coating. A metal organic thin film is formed on the surface of a positive electrode material through molecular layer deposition, the thin film contains a lithium element, the metal organic thin film is a hybrid thin film formed by a metal center and an organic ligand, and the invention further discloses application of the lithium-containing multi-metal composite hydrocarbon derivative polymer coating in a lithium battery positive electrode. The problems that in the prior art, a positive electrode material faces volume change and unstable interface side reaction in the circulation process, and the ionic conductivity of a polymer coating at the present stage is low are solved, so that the mechanical stability and the interface stability of the positive electrode material are improved, ion transmission at an electrode interface is promoted, and the positive electrode performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery positive electrode preparation, and specifically relates to a lithium-containing multi-metal composite hydrocarbon-derived polymer coating. The present invention also relates to a preparation method of the lithium-containing multi-metal composite hydrocarbon-derived polymer coating and the application of the lithium-containing multi-metal composite hydrocarbon-derived polymer coating in a lithium battery positive electrode. Background Art

[0002] As a new type of high-efficiency energy storage device, lithium-ion batteries have been widely used in electric vehicles, portable electronic devices and other fields. With the continuous advancement and development of lithium battery technology, achieving high energy density, high rate performance and long cycle life is one of the important issues at this stage. As for lithium battery positive electrode materials, in addition to layered structure positive electrodes (such as lithium cobalt oxide, lithium manganese oxide), spinel structure positive electrodes (such as LiMn2O4) and olivine structure positive electrodes (such as lithium iron phosphate), new positive electrode materials with higher theoretical capacity include lithium-rich positive electrodes (such as Li(Li x TM 1-x )O2, TM is a transition metal) and a ternary layered oxide positive electrode (such as LiMn x Co y Ni z O2, x+y+z=1) is the preferred cathode material for high energy density lithium-ion batteries. However, these cathode materials face many challenges, including cathode-electrolyte interface, volume change, structural instability, etc. Side reactions with solid electrolytes or electrolytes will form an unstable interface at the cathode interface, increasing the interface impedance. The anisotropic lattice stress suffered during the continuous electrochemical delithiation and insertion process will cause the cathode particles to rupture. In addition, the new surface exposed after the particles are ruptured will undergo continuous side reactions with the solid electrolyte or electrolyte, causing degradation of the cathode material and leading to battery failure.

[0003] Existing technologies show that volume changes, interfacial side reactions and structural instability can be effectively alleviated by constructing an artificial coating on the surface of the positive electrode of a lithium-ion battery. It is extremely difficult to control the thickness, composition and uniformity of the coating layer with traditional high-temperature solid-phase synthesis and wet coating methods. As a new type of thin film deposition technology, molecular layer deposition technology can accurately control the number of deposition cycles and composition to achieve an organic coating layer with good mechanical properties and interface stability. The mechanical properties, chemical stability, ion / electronic conduction and other properties can be adjusted by introducing metal-containing components to form a composite hydrocarbon-derived polymer. However, it is difficult for the composite hydrocarbon-derived polymer formed by the introduction of a single metal to simultaneously take into account multiple properties such as mechanical, chemical, and ion transmission, resulting in limited performance improvement. Therefore, by designing and introducing a variety of different metals and organic components to form a multi-metal composite hydrocarbon-derived polymer coating, it is expected to accurately control the positive electrode interface and achieve an overall performance improvement. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium-containing multi-metal composite hydrocarbon-derived polymer coating, which solves the problems of volume change and unstable interface side reactions faced by positive electrode materials in the prior art during the cycle, as well as the low ion conductivity of the polymer coating at this stage, thereby improving the mechanical stability and interface stability of the positive electrode material, promoting ion transport at the electrode interface, and achieving improved positive electrode performance.

[0005] Another object of the present invention is to provide a method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating.

[0006] The third object of the present invention is to provide the application of lithium-containing multi-metal composite hydrocarbon-derived polymer coating.

[0007] The first technical solution adopted by the present invention is that a lithium-containing multi-metal composite hydrocarbon-derived polymer coating is deposited on the surface of the positive electrode material by molecular layer deposition to form a metal organic film, which contains lithium elements. The metal organic film is a hybrid film formed by a metal center and an organic ligand. In addition to lithium elements, the metal center also contains one or more of Al, Zn, Ti, Sn, Hf, V, Zr, Nb, and Ta.

[0008] The second technical solution adopted by the present invention is a method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating, which is specifically implemented according to the following steps: Step 1.1, place the cathode material into the atomic layer deposition chamber, maintain the chamber temperature at 100~250℃, set the carrier gas flow rate at 5~100 sccm, and the reaction chamber pressure at 100~500 mTorr; Step 1.2, controlling the thickness and composition of the coating by adjusting the amount of precursor, reaction temperature and reaction time to form a uniform protective layer; Step 1.3: Set step 1.2 in the above steps as a complete cycle, repeat M times, and obtain a lithium-containing multi-metal composite hydrocarbon-derived polymer coating.

[0009] The second technical solution of the present invention is also characterized in that: In step 1.1, the positive electrode material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, ternary layered oxide positive electrode, and lithium-rich positive electrode.

[0010] Step 1.2 is as follows: Step 1.2.1, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s, and the purge time to 20-50s; then introducing a precursor A1, setting the pulse time to 0.1-1s, and the purge time to 20-50s, and setting the number of deposition cycles to X; Step 1.2.2, then introduce precursor B1 into the reaction chamber, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A2, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Y times; or after completing the above steps of introducing B1 and introducing A2 and repeating Y times, introduce precursor B2, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A3, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Z times; X, Y, Z, and M are all positive integers and less than or equal to 100.

[0011] In step 1.2.2, before the precursor A3 is introduced, the precursor B2 is introduced. The precursor B2 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum. The preheating temperature is 30-200°C, the pulse time is set to 0.1-1s, and the purge time is 20-50s.

[0012] In step 1.2, the precursors A1, A2, and A3 are any one of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycerol, or glycidol. A1, A2, and A3 may be the same or different from each other, and the preheating temperature is 30 to 200°C. The precursor B1 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum, and the preheating temperature is 30 to 200°C.

[0013] Step 1.2 is as follows: Step 1.2a, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an isocyanate precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; Step 1.2b, introducing precursor B1 into the reaction chamber, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an amine precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an isocyanate precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an amine precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; The lithium source precursor in step 1.2a is any one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, n-butyl lithium, cyclopentadienyl lithium and 2,2,6,6-tetramethyl-3,5-heptanedioate lithium, and the preheating temperature is 30~200°C; the amine precursor is any one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine, and the preheating temperature is 30°C~100°C; the isocyanate precursor is any one or more of 1,4-butyl diisocyanate and phenylene diisocyanate, and the preheating temperature is 30~150°C.

[0014] The third technical solution adopted by the present invention is that the lithium-containing multi-metal composite hydrocarbon-derived polymer coating is applied to the positive electrode of a liquid lithium-ion battery.

[0015] The fourth technical solution adopted by the present invention is that the lithium-containing multi-metal composite hydrocarbon-derived polymer coating is applied to the positive electrode of a solid-state lithium battery.

[0016] The beneficial effect of the present invention is that the multi-metal composite hydrocarbon-derived polymer coating with lithium ion conductivity improves the electrochemical performance of the positive electrode of the lithium ion battery, focusing on solving the problems of interface ion conduction, volume effect of the positive electrode material and unstable interface side reactions. The difficulty of the invention lies in the preparation of a uniform, controllable and multi-component coating. The innovation of the present invention is that a multi-metal composite hydrocarbon-derived polymer coating with lithium ion conductivity is successfully constructed on the positive electrode through molecular layer deposition technology. The thickness and components of this coating can be precisely controlled by the number and sequence of molecular layer deposition turns, thereby realizing the regulation of electrochemical performance. The prepared organic coating has good flexibility and can effectively buffer the volume changes caused by the positive electrode particles during the continuous lithium removal and lithium insertion process, thereby ensuring the cycle life of the positive electrode of the lithium ion battery. The preparation method of the present invention is simple, precisely controllable, has good repeatability, and can be prepared in large quantities. The cycle stability and rate performance of the prepared positive electrode material are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1The hybrid polyurea coating containing lithium and aluminum elements in the present invention coated LiNi0.94Co0.05Mn0.01O2 has a long cycle performance in a voltage window of 2.8 to 4.3V at a rate of 0.5C; Figure 2 The hybrid polyurea coating containing lithium and zinc elements in the present invention coated LiNi0.94Co0.05Mn0.01O2 has a long cycle performance in a voltage window of 2.8 to 4.3V at a rate of 0.5C; Figure 3 The long cycle performance of the LiNi0.83Co0.11Mn0.06O2 positive electrode coated with the lithium-containing bimetallic hybrid organic coating of the present invention at a voltage window of 2.8V to 4.3V at a rate of 0.5C; Figure 4 The solid-state battery prepared by the LiNi0.83Co0.11Mn0.06O2 positive electrode coated with the lithium-containing bimetallic hybrid organic coating in the present invention has long cycle performance in a voltage window of 2.8V to 4.3V at a rate of 0.2C. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] The lithium-containing multi-metal composite hydrocarbon-derived polymer coating of the present invention forms a metal organic film on the surface of the positive electrode material through molecular layer deposition, and the film contains lithium elements, other metal elements, and organic hydrocarbon components. The metal organic film is a hybrid film formed by a metal center and an organic ligand, and the metal center contains one or more of Al, Zn, Ti, Sn, Hf, V, Zr, Nb, and Ta in addition to lithium elements. The composition and thickness of the coating can be precisely controlled by adjusting the order and number of turns of atomic layer and molecular layer deposition.

[0020] The method for preparing the lithium-containing multi-metal composite hydrocarbon-derived polymer coating is specifically implemented according to the following steps: Step 1.1, place the cathode material into the atomic layer deposition chamber, maintain the chamber temperature at 100~250℃, set the carrier gas flow rate at 5~100 sccm, and the reaction chamber pressure at 100~500 mTorr; Step 1.2, controlling the thickness and composition of the coating by adjusting the amount of precursor, reaction temperature and reaction time to form a uniform protective layer; Step 1.3: Set step 1.2 in the above steps as a complete cycle, repeat M times, and obtain a lithium-containing multi-metal composite hydrocarbon-derived polymer coating.

[0021] In step 1.1, the positive electrode material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, ternary layered oxide positive electrode, and lithium-rich positive electrode.

[0022] Step 1.2 is as follows: Step 1.2.1, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s, and the purge time to 20-50s; then introducing a precursor A1, setting the pulse time to 0.1-1s, and the purge time to 20-50s, and setting the number of deposition cycles to X; Step 1.2.2, then introduce precursor B1 into the reaction chamber, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A2, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Y times; after completing the above steps of introducing B1 and introducing A2 and repeating Y times, introduce precursor B2 again, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A3, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Z times; X, Y, Z, and M are all positive integers and less than or equal to 100.

[0023] In step 1.2.2, before the precursor A3 is introduced, the precursor B2 is introduced. The precursor B2 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum. The preheating temperature is 30-200°C, the pulse time is set to 0.1-1s, and the purge time is 20-50s.

[0024] In step 1.2, the precursors A1, A2, and A3 are any one of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycerol, or glycidol. A1, A2, and A3 may be the same or different from each other, and the preheating temperature is 30 to 200°C. The precursor B1 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum, and the preheating temperature is 30 to 200°C.

[0025] Step 1.2 can also be performed according to the following scheme, as follows: Step 1.2a, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an isocyanate precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; Step 1.2b, introducing precursor B1 into the reaction chamber, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an amine precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an isocyanate precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; then introducing an amine precursor, setting the pulse time to 0.1~1s, and the purge time to 20~50s; The lithium source precursor in step 1.2a is any one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, n-butyl lithium, cyclopentadienyl lithium and 2,2,6,6-tetramethyl-3,5-heptanedioate lithium, and the preheating temperature is 30~200°C; the amine precursor is any one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine, and the preheating temperature is 30°C~100°C; the isocyanate precursor is any one or more of 1,4-butyl diisocyanate and phenylene diisocyanate, and the preheating temperature is 30~150°C.

[0026] Lithium-containing multi-metallic composite hydrocarbon-derived polymer coating for use in the positive electrode of liquid lithium-ion batteries.

[0027] Lithium-containing multi-metallic composite hydrocarbon-derived polymer coating for application in solid-state lithium battery positive electrode.

[0028] The thickness and composition of the coating of the present invention can be precisely controlled by adjusting the amount of precursor, reaction temperature and reaction time to form a uniform protective layer, and the preparation method is simple and has good repeatability. The coating has good lithium ion conductivity, can effectively adjust the lithium ion conduction of the positive electrode interface, and takes into account excellent mechanical properties, alleviates the rupture of positive electrode particles caused by volume expansion; blocks direct contact between the electrolyte and the positive electrode material, resists the side reaction of the electrolyte or solid electrolyte, and makes the surface interface stable during battery operation, so that the lithium ion battery positive electrode of the present invention exhibits excellent cycle performance and rate performance.

[0029] The present invention overcomes the challenges of positive electrode interface charge transfer, positive electrode volume change, and interface side reactions, and designs a preparation technology for a multi-metal composite hydrocarbon-derived polymer coating coated positive electrode material with lithium ion conductivity using molecular layer deposition technology. The purpose of the present invention is to solve the problems of volume change and unstable interface side reactions faced by positive electrode materials during the cycle process, as well as the low ion conductivity of polymer coatings at this stage, thereby improving the mechanical stability and interface stability of positive electrode materials, promoting ion transfer at the electrode interface, and achieving improved positive electrode performance.

[0030] Example 1 This embodiment is a hybrid polyurea coating containing lithium and aluminum elements coated with LiNi 0.94 Co 0.05 Mn 0.01 The preparation method of O2 powder is as follows: S1, LiNi 0.94 Co 0.05 Mn 0.01 O2 powder was placed in the atomic layer deposition chamber, the chamber temperature was raised to 150°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0031] S2, the precursor lithium tert-butoxide is introduced with a pulse time of 1s and a purge time of 35s, then ethylenediamine is introduced with a pulse time of 0.1s and a purge time of 35s; then 1,4-butyl diisocyanate is introduced with a pulse time of 1s and a purge time of 35s; then ethylenediamine is introduced with a pulse time of 0.1s and a purge time of 35s; S3, set the pulse time of the precursor trimethylaluminum to 0.1s, the purge time to 35s, then introduce ethylenediamine, set the pulse time to 0.1s, the purge time to 35s; then introduce 1,4-butyl diisocyanate, set the pulse time to 1s, the purge time to 35s; then introduce ethylenediamine, set the pulse time to 0.1s, the purge time to 35s; S4: Take steps S2 to S3 as one cycle, and perform 5 cycles in total.

[0032] S5. Prepare a slurry of the above-mentioned coated positive electrode material, PVDF, C65 and VGCF according to a mass ratio of 90:5:2.5:2.5 to prepare an electrode. The mass loading of the active material is 5 mg / cm 2 .

[0033] S6. Cut the prepared electrode into circular electrode sheets and assemble liquid button batteries using an ester electrolyte.

[0034] Electrochemical performance test: combined Figure 1 , the coated LiNi obtained in this example 0.94 Co0.05 Mn 0.01 O2 was tested for electrochemical performance in button cells with a test voltage range of 2.8-4.3 V. It was activated for three cycles at a current of 0.1 C (1 C = 200 mAh / g) and then cycled at a current density of 0.5 C. LiNi coated with lithium-containing bimetallic hybrid organic coating 0.94 Co 0.05 Mn 0.01 The cycle stability of the O2 positive electrode has been improved. After 500 cycles, its capacity retention rate is 43.1%. 0.94 Co 0.05 Mn 0.01 The O2 cycle capacity retention rate was 29.3%.

[0035] Example 2 This embodiment is a metal hybrid polyurea coating containing lithium and zinc elements coated with LiNi 0.94 Co 0.05 Mn 0.01 The preparation method of O2 powder is as follows: S1, LiNi 0.94 Co 0.05 Mn 0.01 O2 powder was placed in the atomic layer deposition chamber, the chamber temperature was raised to 150°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0036] S2, the precursor lithium tert-butoxide is introduced with a pulse time of 1s and a purge time of 35s, then ethylenediamine is introduced with a pulse time of 0.1s and a purge time of 35s; then 1,4-butyl diisocyanate is introduced with a pulse time of 1s and a purge time of 35s; then ethylenediamine is introduced with a pulse time of 0.1s and a purge time of 35s; S3, set the pulse time of the precursor diethyl zinc to 0.1s, the purge time to 35s, then introduce ethylenediamine, set the pulse time to 0.1s, the purge time to 35s; then introduce 1,4-butyl diisocyanate, set the pulse time to 1s, the purge time to 35s; then introduce ethylenediamine, set the pulse time to 0.1s, the purge time to 35s; S4: Take steps S2 to S3 as one cycle, and perform 2 cycles in total.

[0037] S5. Prepare a slurry of the above-mentioned coated positive electrode material, PVDF, C65 and VGCF according to a mass ratio of 90:5:2.5:2.5 to prepare an electrode. The mass loading of the active material is 5 mg / cm 2 .

[0038] S6. Cut the prepared electrode into circular electrode sheets and assemble liquid button batteries using an ester electrolyte.

[0039] Electrochemical performance test: combined Figure 2 , the coated LiNi obtained in this example 0.94 Co 0.05 Mn 0.01 O2 was tested for electrochemical performance in button cells with a test voltage range of 2.8-4.3 V. It was activated for three cycles at a current of 0.1 C (1 C = 200 mAh / g) and then cycled at a current density of 0.5 C. LiNi coated with lithium-containing bimetallic hybrid organic coating 0.94 Co 0.05 Mn 0.01 The cycle stability of the O2 positive electrode has been improved. After 500 cycles, its capacity retention rate is 36.4%. 0.94 Co 0.05 Mn 0.01 O2 cycle capacity retention rate Figure 1 As shown in the figure, it is 29.3%.

[0040] Example 3 This embodiment contains lithium bimetallic hybrid organic coating coated LiNi 0.83 Co 0.11 Mn 0.06 The preparation method of O2 powder is as follows: S1, LiNi 0.83 Co 0.11 Mn 0.06 O2 powder was placed in the atomic layer deposition chamber, the chamber temperature was raised to 190°C, the carrier gas was set to argon, and the carrier gas flow rate was 20 sccm.

[0041] S2, the precursor lithium tert-butoxide is introduced into the cavity, the pulse time is 1s, the purge time is 20s; set the pulse time of the precursor ethylene glycol to 1s, the purge time is 20s; S3, then into the above-mentioned cavity through the precursor tributyltin hydride, set the pulse time 1s, the purge time is 20s, set the precursor ethylene glycol pulse time 1s, the purge time is 20s; S4. Finally, the precursor tantalum diethylamide is introduced into the above cavity, and its pulse time is set to 1s, and the purge time is set to 20s. The pulse time of the precursor ethylene glycol is set to 1s, and the purge time is set to 20s.

[0042] S5: Take S2~S4 as one cycle, and perform 5 cycles in total.

[0043] S6. Prepare a slurry of the above-mentioned coated positive electrode material, PVDF, C65 and VGCF according to a mass ratio of 90:5:2.5:2.5 to prepare an electrode. The mass loading of the active material is 5 mg / cm 2.

[0044] S7. Cut the prepared electrode into circular electrode sheets and assemble liquid button batteries using an ester electrolyte.

[0045] Electrochemical performance test: combined Figure 3 , the coated LiNi obtained in this example 0.83 Co 0.11 Mn 0.06 O2 was electrochemically tested in button cells with a test voltage range of 2.8-4.3 V. It was activated for three cycles at a current of 0.05 C (1 C = 200 mAh / g) and then cycled at a current density of 1 C. LiNi coated with a lithium-containing bimetallic hybrid organic coating 0.83 Co 0.11 Mn 0.06 The O2 positive electrode showed better cycling stability, with a capacity retention rate of 94.7% after 100 cycles.

[0046] Example 4 In this example, the lithium-containing bimetallic hybrid organic coating prepared in Example 3 is coated with LiNi 0.83 Co 0.11 Mn 0.06 O2 powder assembles solid-state batteries. The specific steps are as follows: S1. The coated positive electrode material and the sulfide electrolyte Li6PS5Cl are uniformly mixed in a mass ratio of 7:3 to obtain a positive electrode mixture.

[0047] S2, 60~80mg sulfide electrolyte Li6PS5Cl was pressed into an electrolyte sheet at a pressure of ~2Ton, the positive electrode mixture was pressed into a positive electrode sheet at one end of the electrolyte sheet at a pressure of ~3Ton, and Li-In alloy was placed at the other end of the electrolyte sheet; the mass loading of active material was ~8.9 mg / cm 2 .

[0048] S3. No liquid electrolyte is used when assembling solid-state batteries, and no external pressurization is applied during electrochemical testing.

[0049] Electrochemical performance test: combined Figure 4 , the coated LiNi obtained in this example 0.83 Co 0.11 Mn 0.06 O2 was tested for electrochemical performance in a mold battery with a test voltage range of 2.8V-4.3V. It was activated for three cycles at a current of 0.05C (1 C = 200 mAh / g) and then cycled at a current density of 0.2C. LiNi coated with a lithium-containing bimetallic hybrid organic coating 0.83 Co 0.11 Mn 0.06The O2 cathode showed better cycling stability.

Claims

1. A lithium-containing multi-metal composite hydrocarbon-derived polymer coating, characterized in that: A metal organic film is formed on the surface of the positive electrode material by molecular layer deposition. The film contains lithium. The metal organic film is a hybrid film formed by a metal center and an organic ligand. In addition to lithium, the metal center also contains one or more of Al, Zn, Ti, Sn, Hf, V, Zr, Nb, and Ta.

2. A method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating, characterized in that: Follow the steps below to implement it: Step 1.1, place the cathode material into the atomic layer deposition chamber, maintain the chamber temperature at 100~250℃, set the carrier gas flow rate at 5~100 sccm, and the reaction chamber pressure at 100~500 mTorr; Step 1.2, controlling the thickness and composition of the coating by adjusting the amount of precursor, reaction temperature and reaction time to form a uniform protective layer; Step 1.3: Set step 1.2 in the above steps as a complete cycle, repeat M times, and obtain a lithium-containing multi-metal composite hydrocarbon-derived polymer coating.

3. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 2, characterized in that: In the step 1.1, the positive electrode material is one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, a ternary layered oxide positive electrode, and a lithium-rich positive electrode.

4. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 2, characterized in that: The step 1.2 is specifically as follows: Step 1.2.1, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s, and the purge time to 20-50s; then introducing a precursor A1, setting the pulse time to 0.1-1s, and the purge time to 20-50s, and setting the number of deposition cycles to X; Step 1.2.2, then introduce precursor B1 into the reaction chamber, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A2, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Y times; or after completing the above steps of introducing B1 and introducing A2 and repeating Y times, introduce precursor B2, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce precursor A3, set the pulse time to 0.1~1s, and the purge time to 20~50s, and repeat this cycle Z times; X, Y, Z, and M are all positive integers and less than or equal to 100.

5. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 4, characterized in that: In the step 1.2.2, before the precursor A3 is introduced, the precursor B2 is introduced, and the precursor B2 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum. The preheating temperature is 30-200°C, the pulse time is set to 0.1-1s, and the purge time is 20-50s.

6. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 4, characterized in that: In the step 1.2, the precursors A1, A2, and A3 are any one of ethylene glycol, propylene glycol, 1,4-butanediol, 1-6-hexanediol, glycerol or glycidol, A1, A2, and A3 may be the same as or different from each other, and the preheating temperature is 30 to 200° C. The precursor B1 is any one of trimethylaluminum, diethylzinc, tributyltin hydride, titanium tetrachloride, tetrakis(dimethylamino)titanium, tetrakis(dimethylamino)hafnium(IV), tetrakis(ethylmethylamino)vanadium(IV), tetra-tert-butoxide zirconium, pentaethoxyniobium, diethylamide tantalum, or pentaethoxytantalum, and the preheating temperature is 30 to 200° C.

7. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 2, characterized in that: The step 1.2 is specifically as follows: Step 1.2a, introducing a lithium source precursor into the reaction chamber, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an isocyanate precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; then introducing an amine precursor, setting the pulse time to 0.1-1s and the purge time to 20-50s; Step 1.2b, introduce precursor B1 into the reaction chamber, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce an amine precursor, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce an isocyanate precursor, set the pulse time to 0.1~1s, and the purge time to 20~50s; then introduce an amine precursor, set the pulse time to 0.1~1s, and the purge time to 20~50s.

8. The method for preparing a lithium-containing multi-metal composite hydrocarbon-derived polymer coating according to claim 7, characterized in that: The lithium source precursor in the step 1.2 is any one or more of lithium tert-butoxide, lithium bis(trimethylsilyl)amide, n-butyl lithium, cyclopentadiene lithium and 2,2,6,6-tetramethyl-3,5-heptanedioate lithium, and the preheating temperature is 30~200°C; the amine precursor is any one or more of aminoethyl sulfide, ethylenediamine, 2,2'-(propane-2,2-diylbis(oxy))diethylamine, tris(2-aminoethyl)amine, diethyltriamine, and triethylenetetramine, and the preheating temperature is 30°C~100°C; the isocyanate precursor is any one or more of 1,4-butyl diisocyanate and phenylene diisocyanate, and the preheating temperature is 30~150°C.

9. A lithium-containing multi-metal composite hydrocarbon-derived polymer coating, characterized in that: Used in positive electrode of liquid lithium-ion batteries.

10. A lithium-containing multi-metal composite hydrocarbon-derived polymer coating, characterized in that: Used in solid-state lithium battery positive electrode.